Design of intelligent trading bookcase based on new electronic control lock - Linyu Guan; Liqiang Zhang; Jiawei Ma; Chunyan Zhang; Meihua Zhang (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
In view of the lack of direct trading devices between students in the second-hand book market, an intelligent trading bookcase based on a new type of electronic control lock is proposed. The structure of the intelligent trading bookcase is designed in detail, and the hardware and control principle are introduced. Finally the physical system is verified with program written in C. All expected functions are working well on human-computer interaction window.